2013
DOI: 10.3109/2000656x.2013.791624
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous anterior interosseous nerve syndrome: clinical analysis of eleven surgical cases

Abstract: The aetiology of anterior interosseous nerve (AIN) syndrome and an optimal treatment strategy remain controversial. Eleven patients with spontaneous AIN syndrome, who were treated by surgical exploration, were reviewed at a mean of 32.5 months after the operation. Eight men and three women were included in the study. None of the patients had a history of trauma and there was no evidence of a neuropathy other than AIN syndrome. Six patients showed complete paralysis of the flexor pollicis longus (FPL) and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…as primary or delayed treatment with varying degrees of success. 5,16,[26][27][28][29] The presence of prodromal pain in many AINS patients and the potential for spontaneous symptomatic resolution, however, are more suggestive of an inflammatory and/or ischemic, rather than compressive, etiology. The frequency of fascicular abnormalities of the median nerve proper described in this and other studies provides further evidence for a noncompressive neuropathy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…as primary or delayed treatment with varying degrees of success. 5,16,[26][27][28][29] The presence of prodromal pain in many AINS patients and the potential for spontaneous symptomatic resolution, however, are more suggestive of an inflammatory and/or ischemic, rather than compressive, etiology. The frequency of fascicular abnormalities of the median nerve proper described in this and other studies provides further evidence for a noncompressive neuropathy.…”
Section: Resultsmentioning
confidence: 99%
“…AINS has conventionally been considered an idiopathic neuropathy of the forearm and several studies have reported forearm decompression as primary or delayed treatment with varying degrees of success . The presence of prodromal pain in many AINS patients and the potential for spontaneous symptomatic resolution, however, are more suggestive of an inflammatory and/or ischemic, rather than compressive, etiology.…”
Section: Discussionmentioning
confidence: 99%
“…The AHFPL may lead to an entrapment neuropathy of the anterior interosseous nerve (AIN), known as Kiloh-Nevin syndrome or anterior interosseous nerve syndrome (AINS) [5,15,25]. This syndrome is manifested clinically as a weakness in flexion of the interphalangeal joint of the thumb and the distal interphalangeal joints of the index and middle finger [18,23,26]. The present study was conducted to evaluate the prevalence of this accessory muscle in a South American population sample, its morphometry and relationship with the AIN, constituting valuable information for clinical diagnosis and surgical approaches to the forearm.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies using surgical decompression have shown symptomatic relief in a number of cases,2 18 19 other studies using conservative management reported full symptomatic recovery up to 18 months after onset of palsy 2 16. In a retrospective study of 14 patients reported by Ulrich et al ,2 eight patients were managed conservatively with near full recovery in all patients, while six patients were managed surgically after not showing any signs of recovery after 3 months.…”
Section: Discussionmentioning
confidence: 97%